2012
DOI: 10.3892/ol.2012.686
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal curcumin inhibits Lewis lung cancer growth primarily through inhibition of angiogenesis

Abstract: Abstract. Curcumin has been proven to effectively inhibit tumor growth by both targeting tumor cells and angiogenesis; however, poor water solubility limits further clinical application. In the present study, we prepared water-soluble liposomal curcumin to investigate its anti-tumor effects and the underlying mechanism. The MTT assay was used to test the anti-proliferative activities for the MS1 murine endothelial and LL/2 Lewis lung cancer cell lines. Apoptosis and cell cycle arrest induced by liposomal curcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The role of propylene glycol in lipid vesicle shape and transdermal procedure at the cellular level should be investigated further. PGL outperformed ethosomes and regular liposomes, suggesting that PGL, as described in this study, are potential carriers for medication delivery to the skin [66][67][68].…”
Section: Antibacterial Activity Of Cur Propylene Glycolmentioning
confidence: 51%
“…The role of propylene glycol in lipid vesicle shape and transdermal procedure at the cellular level should be investigated further. PGL outperformed ethosomes and regular liposomes, suggesting that PGL, as described in this study, are potential carriers for medication delivery to the skin [66][67][68].…”
Section: Antibacterial Activity Of Cur Propylene Glycolmentioning
confidence: 51%
“…The hydroxyl groups present in the chemical structure of curcumin are essential for its antioxidant activity, whereas the methoxy groups are known to have antiproliferative and anti-inflammatory activities . Liposomal curcumin has been used in the treatment of various forms of cancers in vitro and in vivo, including prostate, breast, liver, lung, cervical, and bone cancers. Studies showed that liposomes enhance the biological activity, stability, and anticancer efficacy of curcumin; therefore, curcumin-encapsulated liposome can be considered as an excellent strategy for treating cancers . The mechanism of action of liposomal curcumin involves gradual release of free curcumin from the liposome in the tumor site followed by the uptake of the drug by the malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of phase I and II clinical studies of curcumin in other types of malignancies such as the skin, the liver and pancreatic cancer have not supported the preclinical observations due to the low stability and limited absorption of EGCG [143,144]. An interesting study was conducted by Wang L et al in which they demonstrated the potential anti-cancer effect of using water-soluble liposomal curcumin on Lewis lung cancer in vitro and in vivo by suppressing angiogenesis [145]. This liposomal form of curcumin could overcome problems associated with previous clinical trials and may show a better improvement in the overall survival of cancer patients.…”
Section: Alternative Anti-angiogenic Compoundsmentioning
confidence: 99%